2020
DOI: 10.1111/1753-6405.13039
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and use of telephone‐based behaviour change support services among clients of a community mental health service

Abstract: Objective: To determine the prevalence of, and factors associated with, awareness and use of telephone-based behaviour change support services among clients of a community mental health service. Methods: Adult clients (n=375) of one Australian community mental health service completed a telephone interview and self-reported not meeting Australian National Guidelines for smoking, nutrition, alcohol consumption and/or physical activity. Descriptive statistics summarised awareness and use of the New South Wales Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Although quit line on tobacco packs has been introduced recently in India, a study in 2013 on voluntary local reactive helpline initiated for Tobacco cessation in Rajasthan showed a low awareness among the study population,(13) possibly due to dismal Information, Education and Communication (IEC). This is in contrast to a study by Fehily in 2017 (14) in an Australian community mental health service, wherein a high awareness (89%) and utilisation (18%) of quitline was observed, probably due to the active media campaigns after the introduction of quitline way back in 1997. However, a multivariable logistic regression revealed that no factors were significantly associated with awareness of quitline.…”
Section: Discussioncontrasting
confidence: 97%
“…Although quit line on tobacco packs has been introduced recently in India, a study in 2013 on voluntary local reactive helpline initiated for Tobacco cessation in Rajasthan showed a low awareness among the study population,(13) possibly due to dismal Information, Education and Communication (IEC). This is in contrast to a study by Fehily in 2017 (14) in an Australian community mental health service, wherein a high awareness (89%) and utilisation (18%) of quitline was observed, probably due to the active media campaigns after the introduction of quitline way back in 1997. However, a multivariable logistic regression revealed that no factors were significantly associated with awareness of quitline.…”
Section: Discussioncontrasting
confidence: 97%
“…Participants also offered several ways to ameliorate their concerns, including augmentation of the group with some form of helpline. Elsewhere, telephone helplines have proved to be cost-effective [ 38 ] and particularly suited to supporting people waiting for mental healthcare [ 39 ], making them a viable consideration for this particular service.…”
Section: Discussionmentioning
confidence: 99%